A formal method to analyse human reasoning and interpretation in incident management. (18th August 2008) - Bosse, Tibor; Hoogendoorn, Mark; Jonker, Catholijn M.; Treur, Jan
The study of human reasoning often concentrates on reasoning from an already assumed interpretation of the world, thereby neglecting reasoning towards an interpretation. In the recent literature within cognitive science, the means taken from the area of nonmonotonic logic are proposed to analyse the latter aspect of human reasoning. In this paper, this claim is further worked out and tested against the empirical material of human reasoning during critical situations (incident management). Empirical and simulated reasoning traces have been analysed by comparing them and by automatically checking their properties.